Task-Specific Modulation of Human Auditory Evoked Response in a Delayed-Match-To-Sample Task - Rong, Feng; Holroyd, Tom; Husain, Fatima T.; Contreras-Vidal, Jose; Horwitz, Barry (Frontiers in Psychology, 2011)
In this study, we focus our investigation on task-specific cognitive modulation of early cortical auditory processing in human cerebral cortex. During the experiments, we acquired whole-head magnetoencephalography (MEG) data while participants were performing an auditory delayed-match-to-sample (DMS) task and associated control tasks. Using a spatial filtering beamformer technique to simultaneously estimate multiple source activities inside the human brain, we observed a significant DMS-specific suppression of the auditory evoked response to the second stimulus in a sound pair, with the center of the effect being located in the vicinity of the left auditory cortex. For the right auditory cortex, a non-invariant suppression effect was observed in both DMS and control tasks. Furthermore, analysis of coherence revealed a beta band (12 ~ 20 Hz) DMS-specific enhanced functional interaction between the sources in left auditory cortex and those in left inferior frontal gyrus, which has been shown to involve in short-term memory processing during the delay period of DMS task. Our findings support the view that early evoked cortical responses to incoming acoustic stimuli can be modulated by task-specific cognitive functions by means of frontal-temporal functional interactions.